Financial innovation and financial inclusion nexus in South Asian countries: Evidence from symmetric and asymmetric panel investigation - Md. Qamruzzaman; Jianguo Wei (International Journal of Financial Studies, 2019)
This paper examines the nexus between financial inclusion and financial innovation while incorporating financial development and remittance inflows in the case of six South Asian countries-Bangladesh, India, Pakistan, Nepal, Bhutan, and Srilanka-by employing the panel autoregressive distributed lagged model under a linear and nonlinear framework using monthly data over the period 1990M1-2018M12. Further, a Granger-causality test with System GMM specification was performed for assessing directional causality. The study findings from Panel ARDL confirmed the positive association between financial innovation and financial inclusion, which was observed both in the long run and short-run. Considering the nonlinearity in the estimation, the standard Wald test confirms the existence of an asymmetric relationship both in the short-run and in long run horizon regarding causality test results. The study findings support the feedback hypothesis that the presence of bidirectional causality between the financial innovation and financial inclusion is both in the short-run and long run. Since the study findings established a critical relationship between financial innovation and financial inclusion, therefore effective policy guidelines are suggested so that the contribution from financial inclusion and financial innovation can assist in developing a vibrant financial sector.
Keywords: G21; O16; O31; 330; asymmetry; financial inclusion; financial innovation; ganger-causality; symmetry